Development of civics teaching modules for elementary school teacher education students with pedagogical content knowledge (pck) and growth mindset approaches - Rani Kusuma Ningtyas; Eko Sucahyo; Meliza Meliza; Sabri Sabri (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2026)
This study aims to develop a Civics Education teaching module for Elementary School Teacher Education students at the South Tapanuli Institute of Education that integrates Pedagogical Content Knowledge (PCK) and fosters a growth mindset, and to determine the feasibility and effectiveness of the module in improving students' pedagogical competence and positive attitudes. This study uses Research and Development (R&D) with the ADDIE model, including the stages of Analysis, Design, Development, Implementation, and Evaluation. The research sample consisted of 250 Elementary School Teacher Education students in the 5th semester, divided into 5 classes, with a trial limited to 50 students. Data collection techniques include expert validation, module trials, and student questionnaires to assess pedagogical competence and growth mindset. The results of the study indicate that the developed Civics Education teaching module is feasible to use, with an average expert validation score in the category of Feasible to Very Feasible. The module trial showed an increase in students' pedagogical competence (average score of 79.6, Good category), while the questionnaire results showed the module was effective in fostering a growth mindset (average score of 4.34, Good category). This teaching module was proven to be effective and applicable in Civics learning, and supported the development of students' pedagogical competence and positive attitudes towards learning. This study provides practical implications that the module can be used as an innovative learning medium that improves the teaching quality of Elementary School Teacher Education students.